Effect of Square Dance Exercise on Older Women With Mild Mental Disorders - Chang, Jindong; Chen, Yuping; Liu, Chunzhen; Yong, Liming; Yang, Ming; Zhu, Wenbing; Wang, Jibing; Yan, Jiagao (Frontiers in Psychiatry, 2021)
Many epidemiological studies have demonstrated the therapeutic benefits of exercise (EX) that can be used for adjunctive treatment in mental disorders. Despite several clinical experiments using exercise interventions, controlled studies are sparse in most disorder groups. Square dance is a popular aerobic exercise for older women in China. This study aimed to explore the effect of Chinese square dance exercises on mild mental disorders in older women. Participants included 109 older women with mild cognitive impairment from four large nursing homes. Participants were assigned either to the intervention group (n = 62) or the control group (n = 47), according to their residential nursing home. The intervention group underwent an 18-week square dance exercise, while the control group maintained their usual lifestyle. The outcomes were tested at baseline and weeks 9 and 18. The results showed that square dance exercises positively affected the results of all evaluations, especially on the participants’ depressive symptoms and quality-of-life-related mental health. This study demonstrates that square dance exercise is a safe and effective approach for older women with mild cognitive impairment that benefits their long-term health.